World class manufacturing: an investigation of Hayes and Wheelwright's foundation - Flynn, Barbara B; Schroeder, Roger G; Flynn, E.James (Journal of Operations Management, 1999)
AbstractAlthough Hayes and Wheelwright originally coined the term ‘world class manufacturing’, the global manufacturing environment has undergone many changes since their work. In the study, we seek to determine whether the practices which they described are still relevant in today's manufacturing environment. We also look at their list of competitive priorities and examine whether they function as tradeoffs, as Hayes and Wheelwright suggested, or whether there are synergies between them. The World Class Manufacturing (WCM) Project data set, comprised of plants in the machinery, electronics and transportation components industries, was used to construct measures to correspond to the practices and performance measures suggested by Hayes and Wheelwright. The results indicated that Hayes and Wheelwright's practices were related to competitive performance, and that the addition of new manufacturing practices resulted in further improvements in competitive performance. Thus, Hayes and Wheelwright's practices are robust and have provided a foundation for the use of new manufacturing practices. In addition, there was strong support for the notion that the use of world class manufacturing practices, alone and in combination with new manufacturing practices, leads to the achievement of simultaneous competitive advantages, supporting the synergies perspective.